PENGARUH PEMBERIAN UBI JALAR UNGU (IPOMOEA BATATAS) TERHADAP PENINGKATAN BERAT BADAN IBU HAMIL DENGAN KEKURANGAN ENERGI KRONIS - Suparni Suparni; Fitriyani Fitriyani; Risqi Dewi Aisyah (Siklus : Journal Research Midwifery Politeknik Tegal, 2022)
One of the foods that contain carbohydrates that are quite important in our food security is sweet potatoes. Sweet potatoes contain nutritious substances per 100 grams, namely 123 kcal of energy, 1.8 g of protein, 0.7 g of fat, 27.9 g of carbohydrates, 30 mg of calcium, 49 mg of phosphorus, 0.7 mg of iron, and vitamin A. 7700 SI, vitamin C 22 mg, vitamin B1 0.90 mg. This study aims to determine the effect of giving purple sweet potato (ipomoea batatas) to increase the body weight of pregnant women with SEZ. Purple sweet potato will be given to pregnant women as much as 200 grams (224 calories) per day for 14 days. The type of research conducted is pre-experimental with a pretest-posttest one group design. The population in this study was KEK pregnant women at the Kedungwuni Health Center 2. The sample of this study used random sampling with inclusion criteria. Data collection using the LILA meter. Data analysis using T-Test. The results showed that there was a difference in the weight of pregnant women with KEK before (pre test) and after (post test) given purple sweet potato with a p value of 0.007 ( 0.05). Suggestions for midwives to be able to convey to pregnant women, especially KEK pregnant women about the benefits of this purple sweet potato can help increase maternal weight during pregnancy.Keywords: Purple Sweet Potato, Body Weight, Pregnant Women with chronick lack of energy